Sustainable Active PET Films by Functionalization With Antimicrobial Bio-Coatings - Apicella, Annalisa; Scarfato, Paola; Di Maio, Luciano; Incarnato, Loredana (Frontiers in Materials, 2019)
The realization of antimicrobial films through the incorporation of active agents into a polymer matrix is a promising alternative to the direct addition of antimicrobials into the food matrix. To this aim, the goal of this work was to develop a sustainable, food packaging solution with antimicrobial effectiveness and high functional performance, based on Ethyl-Nα-dodecanoyl-L-arginate (LAE). Active biodegradable coatings, easy soluble to be removed, were realized by spreading a Polylactic acid/LAE coating solution, at different antimicrobial concentration (from 0 to 20%), on a recyclable Polyethylene-terephthalate substrate. The antimicrobial activity of the multilayer films was tested in vitro against E.Coli CECT 434 strain as pathogenic agent in liquid culture media. Moreover, the LAE chemical interaction with the PLA matrix was investigated, as well as its effect on the adhesion, wetting, optical and barrier properties of the films. The results pointed out that that the minimum LAE concentration incorporated already guarantees an antimicrobial activity comparable to commercial antimicrobial packaging solutions, and that, among the systems investigated, 10% LAE is the minimum concentration guaranteeing total inhibition without significantly altering the functionalities of the developed systems.